Can Temporomandibular Joint Disorders Be Diagnosed Beforehand by Assessment of Postural Irregularities? - Canan Dağ; Akif Demirel; Nurhan Özalp (Galenos Yayinevi, 2019)
Aim:In many studies, the relationship between postural status and temporomandibular disorders (TMD) have been investigated, however there is no consensus on this regard. The aim of this study was to investigate the relationship between postural irregularities forward head posture (FHP) and different shoulder levels (DSL) and TMD prevalence in different dentition stages.Materials and Methods:This study, which included children between 4 and 14 years of age attending public schools in Ankara, was planned as a cross-sectional study. Temporomandibular joint (TMJ) was examined intra- and extra-orally. After the examination, the relationship between TMD and body posture (FHP and DSL) was investigated. For statistical analysis, chi-square test and Fisher's exact test were used with significance level of p<0.05.Results:FHP and DSL were statistically related to TMD (p<0.05). In primary dentition, there was no significant relation between FHP and TMD, however, DSL were found to be significantly related to TMD (p<0.05). In mixed dentition, both of these parameters were statistically related to TMD (p<0.05). However, in the permanent dentition, there was no relationship between body posture and TMD.Conclusion:Since there is a strong correlation between postural irregularities and TMD especially in the mixed dentition stage, TMJ and postural status of pediatric patients should be examined as early as possible in the stages of the life. In this regard, the awareness of pediatricians and pediatric dentists to this matter needs to be improved.